Two-Dimensional Semiconductor Heterojunctions for Optoelectronics and Electronics - Wang, Qian; Zhang, Lin; Liu, Xuejuan; Li, Sha (Frontiers in Energy Research, 2021)
Two-dimensional (2D) layered semiconductors are a topic of current research for a wide variety of applications (e.g., electronics, photonics, and optoelectronics) due to their unique ultrathin nature. Here, a review of band alignment engineering in heterojunctions composed of 2D van der Waals (vdW) layered semiconductors and their device applications in optoelectronics are provided. Various approaches induced adjustability of vdW heterojunctions are summarized, mainly including composition and thickness modulations, strain and electric field. Further, their perspectives on future developments in optoelectronics and electronics devices based on the newly unique physical and chemical properties are outlined.